Human Error and Near Misses in Hospital Occupational Safety: A Root Cause Analysis Using HFACS Framework - Hizriansyah, Hizriansyah; Maretalinia, Maretalinia (Open Access Health Scientific Journal, 2025)
Background: Occupational health and safety (OHS) at hospitals is at high risk of near-miss events and human error, both of which have an influence on healthcare workers' safety and service quality. Although many hospitals have technical SOPs, problems still occur because the underlying reasons are rarely properly investigated. The Human Factors Analysis and Classification System (HFACS) framework can assist uncover the underlying causes of accidents, however its implementation in Indonesian hospitals is limited.Methods: This study used a qualitative case study methodology and a root cause analysis technique based on HFACS. Data were gathered over a six-month period by reviewing near-miss occurrence reports and conducting in-depth interviews with seven key informants at Patut Patuh Patju Hospital in West Lombok. Thematic analysis was carried out using NVivo, with data triangulation and member verification.Results: A total of 27 near-miss occurrences were discovered, with root cause patterns spanning all four levels of HFACS: risky acts, preconditions for unsafe acts, insufficient supervision, and organizational impacts. SOP breaches, weariness from heavy workloads, inadequate supervision, and an incident reporting culture that did not yet support the program were among the most significant issues.Conclusion: The deployment of HFACS successfully maps the interactions that produce OHS events at all levels in hospitals. These findings highlight the need of transforming the workplace safety culture into a non-punitive learning culture, which is supported by active supervision, continuing training, and work management rules that are more sensitive to tiredness concerns.